Pregnancy Followed by Delivery May Affect Circulating Soluble Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Levels in Women of Reproductive Age - Mehmet Balin; Ahmet Çelik; M. Ali Kobat; Adil Baydas (Mediators of Inflammation)
Background/Objective. It is known that menopause or lack of endogenous estrogen is a risk factor for endothelial dysfunction and CAD. Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is involved inmultiple phases of vascular dysfunction.The purpose of the current study was to determine the association between soluble LOX-1 (sLOX-1) and pregnancy followed by delivery in women of reproductive age. Materials/Methods. Sixty-eight subjects with pregnancy followed by delivery (group 1) and 57 subjects with nongravidity (group 2) were included in this study. Levels of sLOX-1 were measured in serum by EL SA. Results. Plasma levels of sLOX-1 were significantly lower in Group 1 than Group 2 in women of reproductive age (0.52±0.18 ng/mL and 0.78±0.13, resp., 𝑃<0.001). There were strong correlations between sLOX-1 levels and the number of gravida (𝑟=−0.645, 𝑃<0.001). The levels of sLOX-1 highly correlated with the number of parous (𝑟=−0.683, 𝑃<0.001). Conclusion. Our study demonstrated that serum sLOX-1 levels were associated with pregnancy followed by delivery that might predict endothelial dysfunction. We conclude that pregnancy followed by delivery may delay the beginning and progress of arteriosclerosis and its clinical manifestations in women of reproductive age.